복합화학요법을 받은 미만성 거대 B세포 림프종 환자의 호중구감소증 발생에 영향을 미치는 요인: 환자-대조군 연구 - 임수연(Lim, Su Yeon); 최자윤(Choi, Ja Yun) (Asian oncology nursing, 2022)
Purpose: This study aimed to identify the factors associated with chemotherapy-induced neutropenia (CIN) in diffuse large B-cell lymphoma (DLBCL) patients undergoing combination chemotherapy. Methods: A total of 111 patients with DLBCL participated in this study at C University Hospital. The CIN group consisted of patients with an absolute neutrophil count (ANC) lower than 1,000 cells/μL. Clinical factors, the level of depression, and the level of healthy lifestyle were measured on the chemotherapy administration day, and the ANC was measured on the next follow-up day. Results: Binary logistic regression analysis showed that the factors associated with CIN in DLBCL were the presence of B symptoms at diagnosis (β=4.69) and low-risk CIN regimen (β=0.10) among clinical factors, and the level of healthy lifestyle (β=0.17). Conclusion: Oncology nurses have to focus on the patients vulnerable to CIN having B symptoms at diagnosis, receiving a low-risk CIN regimen, and showing non-adherence to healthy lifestyle practice. Administration of granulocyte colony-stimulating factor can be considered for the patients receiving low-risk CIN regimen to reduce CIN. Education programs including healthy lifestyle practice to improve the immune system should be applied to the DLBCL patients. KCI Citation Count: 0